Pemberdayaan Komunitas Basis Gerejawi (KBG) dengan Pendekatan Appreciative Inquiry (AI) - Rexi Alfrids Baptista Kawuwung (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
A primary and real community within the Church that originates from the laity is known as the Basic Ecclesial Community (BEC). Each BEC has its own qualities and distinctiveness as a basic or grassroots community, both in togetherness and diversity. Togetherness and similarity become the defining characteristics of the communio, where members not only